KARAKTERISTIK TERMAL HIDRODINAMIK UNTUK ALIRAN LAMINAR DAN TURBULEN DI DALAM PIPA DENGAN BERBAGAI BENTUK SISIPAN PLAT BERGALUR - Syaiful, Syaiful; Dzulhimam, Faza (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2015)
The purpose of this study is to investigate the thermal and hydrodynamic characteristics of air flowing in tubes with various inserts of grooved plate. Inserts of grooved plate with a variety of attack angles (a = 0°, 45° and 90°) has been studied in laminar and turbulent flow. Plate inserts are installed inside the tube intended to improve the heat transfer due to the mixing of the fluid. Numerical simulation of three-dimensional flow set as a model in the direction of fluid flow. The working fluid in the tube is cold, whereas hot wall temperature is kept constant. The results showed that the grooved plate inserts increases the heat transfer in the tube. For laminar flow, the highest heat transfer enhancement is obtained at the grooved plate inserts α = 45° i.e. from 4.46 to 20.34% with an increase in friction factor of 172.19 to 204.36%. As for the turbulent flow, the highest heat transfer improvement is found in a grooved plate inserts with α = 45° i.e. from 38.67 to 56.1% with an increase in friction factor of 183.5 to 262.29%.